Connecting Colombia’s protected areas: Using a functional approach for tapir species - Federico Mosquera-Guerra; Sebastian Barreto; Juan D. Palencia-Rivera; Alexander Velasquez-Valencia; Hugo Mantilla-Meluk; Gustavo A. Bruges-Morales; Alex M. Jiménez-Ortega; Fernando Trujillo; Dolors Armenteras-Pascual (PLoS ONE, 2025)
Colombia is the world’s fourth most biodiverse country for mammal species. This condition is evidenced in the high number of mammal species reported in specific groups, such as tapirs. The country is considered a hotspot for the genus Tapirus, reporting three of the four species scientifically valid (Tapirus bairdii, T. pinchaque, and T. terrestris). Approximately ~ 49% of Colombia’s natural ecosystems have been transformed by human activities, and  ~  16% of the national territory is designated protected areas (PAs). In this context, the ecological connectivity between PAs is essential to improve the conservation of threatened large mammals such as tapirs and to contribute to the effectiveness of management of these areas in the current scenario of global change. We developed connectivity models for the tapir species and identified critical areas to conserve and improve ecological connections between PAs in Colombia. To this end, we constructed (i) distribution models for tapir species, (ii) movement resistance surfaces, and (iii) mapped least-cost corridors (LCCs). We also used the circuit and least-cost models to locate conservation priorities and restoration opportunities, estimating the equivalent connected area (ECA) index. Our results provide a national-level assessment of functional connectivity priorities for tapir species. This assessment could be considered as an input to guide efforts related to conservation, restoration, and implementation of management tools that facilitate the movement of tapirs through transformed landscapes. Implementing of these actions could contribute to meeting the goals of the post-2020 global biodiversity framework, which aims to achieve effective, ecologically representative, well-connected, and equitably managed PAs.